A prospective study of surgical site infection of orthopedic implant surgeries - Thahir, Muhammad; Gandhi, Suresh; Kanniyan, Kalaivanan; Kumar, Ravi (International Journal of Research in Orthopaedics, 2017)
Background: Surgical-site infection accounts for approximately 10% of all hospital-acquired infections, which are estimated to double the cost of care and result in an additional mean of 6.5 days of hospital stay. We did prospective study of surgical site infection of orthopaedic implant surgeries. Methods: The aim of the study is to assess the clinical and microbiological outcome of 125 patients who had open reduction and internal fixation with implants and prosthesis at Southern Railway Hospital from January 2006 to January 2007, and its strength of association with major risk factors using univariate analysis. In our study, Patients were allocated in to three groups as NINS risk index group 0, 1 and 2 with risk factors as duration of surgery >2 hours and ASA class ≥3. Post-operative wound infection was diagnosed based on the criteria of Center of Disease Control and assessed for the period of 6 weeks using National Nosocomial Infections Surveillance Risk Index. Results: There were 87 male and 38 females in the study. From 125 Patients, 13 patients had post-operative superficial surgical site infection and presented within 21 days of operation. The infection rate was 10.4%. Two Patients developed deep infection after 6 weeks of study. All the cases with superficial infection were followed at regular intervals, 11 cases resolved with regular dressing and antibiotics but 2 cases continued to discharge sinus up to 3 months. Conclusions: The study showed that the risk of infection rate increased significantly with ASA score, duration of surgery, obesity and NINS risk index. There was no significant association of infection rate with age, diabetes and smoking.